231k views
0 votes
Simplify 3-b(7b+ 2) + 3b - (11 – b).

A.)-7b2 + 2b - 10
B.)-7b2 + 2b -8
C.)8b - 6
D.)-5b -8

2 Answers

0 votes

Answer:

The Answer is gonna be B) -7b2 + 2b -8

Explanation :

= 3-b(7b+ 2) + 3b - (11 – b).

= -7b2 +

=7b2 - 2b +3b +b - 11 + 3

= 3- 7b2 - 2b + 3b- 11+ b

= 7b2 +2b - 8

Sorry I corrected my mistake and B was the right Answer :3

This is the right Answer :3

I hope you are having a great day ❤️❤️❤️❤️❤️

User Bmaddy
by
6.1k points
3 votes

Answer:

B

Explanation:

User Atiq Ur Rehman
by
5.0k points